ANALISA BANGKITAN PERJALANAN PADA PERUMAHAN ELEKTRIK MAS DI KOTA SAMARINDA - HARNOTO, RIKO (KURVA S JURNAL MAHASISWA, 2017)
From the existing phenomenon, there are problems that occur due to the rapid growth of population of Samarinda city, such as transportation problems including the increasing number of trips raised by the electric housing area of the mas can impact on the capacity of existing road service around the residential location.The purpose of this study was to obtain a trip generation model on the electrical housing of the mas and to know the result of the test value of R2 and the F test value, which is expected to be used to estimate the number of trip generations in the electrical housing of the city of Samarinda.Primary data obtained from the results of quisionary dissemination done by simple random sampling technique, while secondary data obtained from the RT 025 and RT 029 in the form of data 500 family head. The method used for this study uses multiple linear regression analysis with SPSS program version 22.0 used to perform calculations.The result of analysis of trip generation model is obtained by model form Y = 0,210 + 0,124 (X4) + 0,465 (X7) + 0,152 (X10) having value of R2 equal to 0,530 indicating level relation of dependent variable with independent variable at strong correlation level means that the correlation between the independent variable (X4) the number of family members, (X7) the reason you use the vehicle and (X10) the cost of gasoline against the (dependent variable) user of vehicle type (Y) has a strong correlation of 53% and the test value F (F calculate> F table) (12,498> 2,70).